Development of a Punching Pad Stand for Athletes in Martial Arts Sports - Sukendro Sukendro; Fitri Diana; Yonifia Anjanika (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The development of facilities for self-defense training is increasing rapidly, but researchers see that there are still no facilities for training kick and punch reactions, especially in martial arts sports, which use manual methods with signals as a stimulus through the sense of hearing in training kick and punch reactions in athletes, apart from that, researchers have also not seen any punching pads that use electrical components based on random flip-flops arranged in a microcontroller circuit as a means of training punch and kick reaction speed in martial arts sports. This research aims to develop facilities or media for the physical components of kicks and punches in the form of a punching pad stand with electric technology based on random flip-flops for the Jambi City martial arts sport. The development of punching pad stands is included in research and development. The punching pad stands for martial arts sports was developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluations) development model. This development research resulted in an Electric Punching Pad Stand product based on Random Flip-Flops and trials have been carried out in both small-group trials and large-group trials. The results of the large group trial were that the product received a percentage score of 84.77% from the comfort aspect, 81.52% from the performance aspect, and 83.53% from the appearance aspect. Meanwhile, for the average accumulated value of the three aspects above, the product received an average value of 83.27% and can be categorized as "Decent" with the criteria "Good".